Influence of secondary phase particles Al2O3/SiC on the microstructure and tribological characteristics of AA7075-based surface hybrid composites tailored using friction stir processing. (January 2021) - Suganeswaran, K; Parameshwaran, R; Mohanraj, T; Radhika, N
Recently, cylinder liners of automotive and aircraft engines are encountered severe wear due to piston slap occurred by the repeated sliding stroke of piston. This research focuses on providing an alternative material for cylinder liners, which can be obtained through friction stir processing on AA7075 with different weight ratios of reinforcements like Al2 O3 and SiC. Friction stir processing is executed with a tool rotational speed of 1000 r/min and traveling speed of 56 mm/min at 2° tool tilt angle. The images of optical microscopy reveal the fine-grains with a homogeneous distribution of secondary phase particles and also offer decrement in particle clustering except at some localized regions. It is identified that addition of 3.7 wt.% Al2 O3  + 3.0 wt.% SiC in AA7075 enhanced the microhardness about 33.96% higher than base matrix. Hence, wear resistance of the specimen is improved. Dry sliding wear behavior of specimens is analyzed using pin on disc at 20, 40, and 60 N load conditions to create the actual sliding behavior of piston on cylinder wall. Increasing the wt.% of Al2 O3 particles enhanced the wear resistance of AA7075 surface hybrid composites at 20 N load due to the formation of protective tribofilm. Specimen with 3.7% Al2 O3  + 3.0% SiC has better lubrication and load-bearing capacity that exhibits superior tribological behavior at 40 and 60 N. Higher Fe content of 5.44 wt.% has been obtained through spectroscopy analysis in S5, which is 8% and 6% higher than S3 (7.5% of Al2 O3 ) and S7 (6% of SiC), respectively. The scratching action of this hard specimen on the counterpart brings more Fe content. Increase of Al2 O3 particles paved the way for tribofilm formation and identified through scanning electron microscopy micrographs. The observation from worn specimens shows that finer wear debris had increased by adding more quantity of SiC particles due to abrasive wear mechanism.